The Effect of Glutamine Supplementation on Microbial Invasion in Surgical Infants Requiring Parenteral Nutrition: Results of a Randomized Controlled Trial. Issue 1 (9th September 2019) - Bishay, Mark; Simchowitz, Venetia; Harris, Kathryn; Macdonald, Sarah; De Coppi, Paolo; Klein, Nigel; Eaton, Simon; Pierro, Agostino; ,
Abstract: Background: To determine whether parenteral plus enteral glutamine supplementation influences microbial invasion in surgical infants who require parenteral nutrition (PN). Methods: An prospective double‐blind randomized controlled trial studying surgical infants receiving PN for at least 5 days for congenital or acquired intestinal anomalies (2009–2012) was used. Infants were randomized to receive either glutamine supplementation (parenteral plus enteral; total 400 mg/kg/d) or isonitrogenous control. The primary end point was microbial invasion evaluated after 5 days of supplementation and defined as: (i) positive conventional blood culture, (ii) evidence of microbial DNA in blood (polymerase chain reaction), (iii) plasma endotoxin level ≥50 pg/mL, or (iv) plasma level of lipopolysaccharide binding protein ≥50 ng/mL. Data are given as median (range) and compared by logistic regression. Results: Sixty infants were randomized and reached the primary end point. Twenty‐five patients had intestinal obstruction, 19 had abdominal wall defects, and 13 had necrotizing enterocolitis. Thirty‐six infants showed evidence of microbial invasion during the study, and 17 of these were not detected by conventional blood culture. There was no significant difference between the 2 groups in the primary outcome; evidence of microbial invasion after 5 days was found in 9/31 (control group) and 8/29 (glutamine group) (odds ratio 0.83 [0.24–2.86; P  = 0.77]). Conclusion: More than half of surgical infants requiring PN showed evidence of microbial invasion. Approximately half of this was not detectable by conventional blood cultures. Parenteral plus enteral glutamine supplementation had no effect on incidence of microbial invasion.